BLEOMYCIN INDUCED FLAGELLATE DERMATITIS IN A PATIENT WITH NON-SEMINOMA GERM CELL TUMOUR WITH BILATERAL UNDESCENDED TESTES - Khan, Manzoor; Hasnat Ul Hassan Khan, Malik; Khan, Muhammad Firdous; Ahmad, Syed Aftab; Baloch, Sara; Asim, Shazia; Akhlaque, Eesha (Journal of Ayub Medical College Abbottabad, 2024)
Flagellate Dermatitis (FD) is a rare cutaneous manifestation of bleomycin toxicity caused by the deficiency of bleomycin hydrolase enzyme in the skin. It typically presents as erythematous patches or papules with linear, multiple flagellate structures. In this article, we report the case of FD in a 21-year-old male patient with non-seminoma germ cell tumour presenting with abdominal pain and bilateral undescended testes since birth. The patient was started on the BEP (Bleomycin, Etoposide and Cisplatin) protocol as per institutional guidelines. On the 17th day of the first cycle, the patient developed multiple whiplash skin lesions over his back, shoulders and front right frontotemporal area with intense itching. A diagnosis of FD was made clinically. Bleomycin was stopped and he was switched to etoposide and cisplatin-based chemotherapy for the remaining three cycles. The rashes were treated with topical steroids (Beclomethasone), Systemic steroids (Prednisolone) and antihistamines (Cetrzine) according to recommended protocol. The patient responded very well to the above-mentioned treatment with the rashes completely disappearing within a span of 14 days. This case highlights the need for vigilance during chemotherapy as it can cause a wide range of skin reactions. FD is a condition with multiple potential causes and mechanisms underlying cutaneous manifestations. Early recognition and prompt treatment can help prevent long-term complications and improve patients’ quality of life.